Values education for the initial teachers’ training of basic education in México - Azucena Ochoa Cervantes; Salvador Peiró i Gregòri (Revista Electrónica Interuniversitaria de Formación del Profesorado)
The article begins contextualizing theoretically the performance in values for teacher education, in order to define the criteria to make the analysis. Then analyzes the Mexican model of initial training of teachers. After an exegesis of legislation and technical documents, it lists the eight competencies to develop during the six grades of primary education, these are: 1) knowledge and care of himself, 2) self-regulation and responsible exercise of freedom, 3) respect and appreciation for diversity 4) sense of belonging to the community, nation and humanity, 5) management and conflict resolution, 6) social participation and policy, 7) attachment to the legality and 8) sense of Justice, understanding and appreciation for democracy. These are the keys to raise demands to train teachers. Then is carried out a mid-term discussion, between the two theoretical sections initials. Thus becomes to contrast - ought to reality. This is done through a case study. The conclusions follow this. And ends with proposals and references used.